An in vivo RNAi mini-screen in Drosophila cancer models reveals novel potential Wnt targets in liver cancer - İpek Even; İzzet Akiva; Necla Birgül İyison (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Aberrant activation of the Wnt/β-catenin signaling, which arises from the accumulation of mutant β-catenin in the cell, is one of the most common driving forces in hepatocellular carcinoma (HCC). We previously identified several genes that are regulated on the overexpression of β-catenin in the HCC cell line that are suggested to be novel Wnt/β-catenin targets playing effective roles in cancer. The aim of the present study was to elucidate the roles of these putative target genes in tumorigenesis with an in vivo analysis in Drosophila. Materials and Methods: We selected 15 genes downregulated in two Drosophila cancer models. Results: The results from the RNAi mini-screen revealed novel roles for the analyzed putative Wnt/β-catenin target genes in tumorigenesis. The downregulation of the analyzed nine genes led to tumor formation as well as metastasis in Drosophila, suggesting a tumor suppressor function. On the other hand, the knockdown of the other two genes suppressed tumor and metastasis formations and disturbed the development of the analyzed eye tissues, indicating an oncogenic or developmental role for these genes. Conclusion: These findings could serve to identify novel subjects for cancer research in order to provide insight into the diagnostic and therapeutic processes of several cancer types. Cite this article as: Even İ, Akiva İ, Birgül İyison N. An in vivo RNAi mini-screen in Drosophila cancer models reveals novel potential Wnt targets in liver cancer. Turk J Gastroenterol 2019; 30(2): 198-207.